2018
DOI: 10.1128/jvi.01260-18
|View full text |Cite
|
Sign up to set email alerts
|

Differential Mechanisms for the Involvement of Polyamines and Hypusinated eIF5A in Ebola Virus Gene Expression

Abstract: Polyamines and hypusinated eIF5A have been implicated in the replication of diverse viruses; however, defining their roles in supporting virus replication is still under investigation. We have previously reported that Ebola virus (EBOV) requires polyamines and hypusinated eIF5A for replication. Using a replication-deficient minigenome construct, we show that gene expression, in the absence of genome replication, requires hypusinated eIF5A. Additional experiments demonstrated that the block in gene expression u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 31 publications
(36 reference statements)
0
36
0
Order By: Relevance
“…In addition, hypusination of eIF5A, a unique posttranslational modification of an aminobutyl moiety from the spermidine at the Lys50 site via deoxyhypusine synthase (DHPS), is necessary for viral protein translation (Olsen and Connor, 2017). As a result, reducing the levels of spermidine by DFMO treatment can also inhibits the expression of EBOV minigenome (Olsen et al, 2016(Olsen et al, , 2018. In our research, we revealed that DFMO reduces the HBc protein levels by promoting its ubiquitination (Figure 6), as a consequence, inhibiting HBV capsids levels and DNA replication (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hypusination of eIF5A, a unique posttranslational modification of an aminobutyl moiety from the spermidine at the Lys50 site via deoxyhypusine synthase (DHPS), is necessary for viral protein translation (Olsen and Connor, 2017). As a result, reducing the levels of spermidine by DFMO treatment can also inhibits the expression of EBOV minigenome (Olsen et al, 2016(Olsen et al, , 2018. In our research, we revealed that DFMO reduces the HBc protein levels by promoting its ubiquitination (Figure 6), as a consequence, inhibiting HBV capsids levels and DNA replication (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to roles in polymerase activity, CHIKV, ZIKV, and HCV translation rely on polyamines, as DFMO-treated (polyamine depleted via ODC1 inhibition) cells exhibited reduced viral translation [43,47]. Further work in Ebola virus (EBOV) and Marburgvirus (MARV) highlighted that polyamines function in transcription from viral genomes, but the translation of these transcripts relied on polyamines through eIF5A hypusination ( Figure 3) [48,49]. The knockdown of eIF5A or inhibition of the enzymes involved in its hypusination resulted in significant decreases in the accumulation of viral proteins.…”
Section: Polyamines In Mammalian Viruses and The Response To Infectionmentioning
confidence: 99%
“…A recent review summarizes the promise of these molecules as antiviral agents [85]. Studies by Olsen and colleagues [48,49] demonstrated the efficacy of these inhibitors against Ebola virus infection, and prior work showed that HIV-1 is similarly sensitive to this group of inhibitors [86]. In sum, several polyamine-targeting molecules show activity against viruses, and further work into their mechanisms of action, toxicity, and in vivo activity is required for the possibility of targeting polyamines to treat or prevent viral infection.…”
Section: Targeting Polyamines As An Antiviral Therapymentioning
confidence: 99%
“…Hsp90 inhibitors demonstrate inhibition of EBOV in cell culture, likely through the destabilization of EBOV L [23,62]. It has also been demonstrated that inhibition of polyamine biosynthesis, such as by 2-difluoromethylornithine (DFMO), and hypusination, by N1-guanyl-1,7-diamineheptane (GC7) and ciclopirox, reduces EBOV replication [63,64].…”
Section: Targeting Filovirus Rna Synthesismentioning
confidence: 99%